Calculate the limit as x-->pi/4 of [tan(x-pi/4)+1]/x-pi/4
lim h-->0 of [f(x+h)-f(x)]/h = f'(x)
lim x--->a [f(x)-f(a)]/(x-a) = f'(x)
The Attempt at a Solution
I've attempted to turn this equation into the form f(x)-f(a)/x-a by letting f(x)=tanx and a=pi/4
This turns into -[-tan(x+a)-tan(a)]/x-a...which isn't the correct derivative form. .I've tried other methods which also turn into similar garble (a minus sign backwards, x-h rather than x+h and the like).
Can anyone see what the problem is? Thanks